Mejoramiento genético y actividades relacionadas. Actividades relacionadas. Perú - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1987)
In 1986 the project in Peru concentrated on 3 main activities: genetic improvement, seed production, and scientific training. The most significant advances in the coastal region consisted of the introduction of 35 advanced Canario type, BCMV-resistant bean lines. These lines were also evaluated in on-farm trials to determine which to release officially. The production of basic bean seed was promoted in Lambayeque, Arequipa, Cajamarca, and Valle de Chincha, and more than 150 ha were planted. Six scientists of the Instituto Nacional de investigaciones y Promocion Agraria working on beans, participated in training courses given at CIAT, and others took courses in Peru. (CIAT)